Isolated Congenital Coronary Ostial Stenosis in a Young Infant: A Case Report. Issue 5 (September 2020) - Miette, Ambra; Nuri, Halkawt Ali; Pomé, Giuseppe; Marasini, Maurizio; Santini, Francesco
Coronary ostial stenosis is a rare congenital cardiac anomaly, frequently associated with hypoplasia of the proximal coronary artery. This condition is potentially life-threatening, as it may present with myocardial ischemia and sudden death. We present a case of left coronary ostial stenosis in a 48-day-old infant symptomatic for sudden cardiac arrest, who successfully underwent surgical angioplasty. Any cardiac arrest in a neonate or young infant should raise suspicion of coronary ostial stenosis/atresia, considering the difficulty in diagnosing this congenital heart defect.